Teaching critical thinking as a stand-alone course: A case study in the Indonesian ELT context - Ajeng Inayatul Ilahiyah (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the pedagogical practice of teaching Critical Thinking (CT) as an independent course within the context of English Language Teaching (ELT). A qualitative research approach was employed to obtain in-depth, context-rich data. The research was conducted in a Critical Thinking and Problem Solving (CTPS) course within the English Education Department at a higher education institution. Data were collected through three complementary methods: semi-structured interviews, classroom observations, and document analysis. The findings reveal that students were introduced to the fundamental concepts of critical thinking and were systematically trained to become critical thinkers through explicit instructional approaches. The explicit instruction model enabled learners to develop structured reasoning skills and apply analytical frameworks to authentic problems. Students' critical thinking achievement was assessed using an argumentative writing grading rubric adapted from the Utah ELA Core Academy, which evaluates the clarity, coherence, and logical strength of written arguments. Based on these findings, this study recommends that critical thinking be offered as a stand-alone course across higher education institutions. Such an approach ensures that students receive dedicated, systematic training in higher-order thinking skills, which are essential for academic success and professional readiness. Incorporating CT as an independent component within curricula addresses a critical gap in preparing graduates to navigate complex, real-world challenges effectively.